The House of Representatives Supervision As The Initial Instrument to Impeachment The President and Vice President - Widodo, Hananto; Puspoayu, Elisabeth Septin; Lovisonnya, Intan; Sulaksono, Sulaksono (IKIP Widya Darma Surabaya, 2024)
Objective: The mechanism for dismissing the President and/or Vice President in Indonesia is regulated by the 1945 Constitution. This process is initiated by the House of Representatives submitting a proposal to the People's Consultative Assembly, stipulating that the President and/or Vice President has violated the provisions in Articles 7A and 7B, and this must be proven first by the Constitutional Court through examination and proof. If it is proven that the President and/or Vice President has violated these provisions, the results of the Constitutional Court trial will be submitted to the People's Consultative Assembly. Subsequently, the People's Consultative Assembly is obliged to hold a trial to decide whether the President and/or Vice President will be impeached. Article 7A of the 1945 Constitution of the Republic of Indonesia regulates the impeachment of the president and the provisions related to the presidential office in Indonesia. Method: According Mahmud Marzuki, this normative legal research, as it is defined entails the process of finding, comprehending and solving legal problems embracing the practice rather its theory. This work in particular focuses on the way in which the House of Representatives can investigate and possibly remove the President and Vice President from their offices. Result: Some of the author's findings related to the essence of impeachment in the Indonesian constitution are, first, to maintain a system of checks and balances in the presidential office through oversight. Second, the direction of the presidential impeachment regulations needs to be improved by clarifying the reasons and mechanisms for impeachment, aiming to avoid dismissing the president for political rather than legal reasons. Novelty: The present study also analyzes the Indonesian Constitution of 1945 about presidential removal from office, stressing the weak legal rationale as well as the appropriate procedure to remove a president to avoid the potential manipulation for political gains. This calls for regulatory improvement to improve checks and balances in order to prop up a better legal framework of fair and constitutional presidential accountability.